Analisa Total Productive Maintenance Dengan Menggunakan Metode Overall Equipment Effectiveness Di Pt. Karung Emas - Ahmad Amir Hamza (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
PT. Karung Emas is a company engaged in the production of sacks that can not be separated from issues related to the effectiveness of the machinery / equipment. In the sack production process is divided into two processes, namely the processes innerbag and process outerbag. Equipment or machinery used in the production process is the extruder outerbag, circularweafing loom, printing and sewing. Total Productive Maintenance (TPM) is a principle of management to improve production efficiency for Improver handling and maintenance of the machine will lead to losses so that the measurement using the Overall Equipment Effectiveness (OEE) followed by measurement of OEE six big losses, breakdown losses, set-up and adjustment losses, reduced speed losses, idling and minor stoppages, rework scarp losses and yield losses. With a Cause and Effect Diagram can be analyzed real problem that the main cause of the high losses that resulted in low labor circularweafing machine loom. Processing results on a machine loom circularweafing known that the OEE for the period January 2015 - May 2015 ranged from 42.96% to 80.83%. This condition indicates that the engine's ability circularweafing loom in the use of machinery / equipment has not reached the ideal condition (≥85%). As for affecting the value of OEE and a top priority for the company is a factor eliminated idling and minor stoppages amounted to 38.98% and the breakdown of 00:09% loss.